2006
DOI: 10.1063/1.2357027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of connectivity, flux pinning, and upper critical field contributions to the critical current density of bulk pure and SiC-alloyed MgB2

Abstract: Ќ transition is more appropriate for untextured samples than the bottom or 10% point on the small-current-density, resistive H c2 transition which corresponds to H c2 ʈ . However, the resistive H c2 transition is still useful for measuring the breadth of the parallel H c2 transition ⌬H, which may be indicative of inhomogeneity in composition in the sample. Hopes for expanding the useful range of MgB 2 are encouraged by earlier work that has shown that H c2 ʈ ͑0͒ can exceed 70 T in C-doped MgB 2 thin films, 2 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
117
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 15 publications
10
117
4
Order By: Relevance
“…2͑b͔͒, in agreement with very recently reported data. 28 Matsumoto et al 26 reported a similar to our record H c2 ͑0͒ value for a SiC-doped MgB 2 tape prepared by the powder-in-tube ͑PIT͒ method. These results correspond to a PIT tape sample that probably has some texturing [31][32][33] and the reported H c2 data were measured with the applied field parallel to the tape.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…2͑b͔͒, in agreement with very recently reported data. 28 Matsumoto et al 26 reported a similar to our record H c2 ͑0͒ value for a SiC-doped MgB 2 tape prepared by the powder-in-tube ͑PIT͒ method. These results correspond to a PIT tape sample that probably has some texturing [31][32][33] and the reported H c2 data were measured with the applied field parallel to the tape.…”
Section: Methodssupporting
confidence: 65%
“…Although the effect of carbon substitution is one of the most studied in MgB 2 , the results on C solubility and the effect of C doping on T c , J c , and H c2 reported so far vary significantly, due to precursor materials, fabrication techniques, and processing conditions used. [20][21][22][23][24][25] Recently, Matsumoto et al 26 reported that J c in SiC-alloyed MgB 2 tapes depends on a complex relation between grain connectivity, H c2 , and flux pinning induced by grain boundaries and precipitates. However, the distinct effect of C incorporation through different routes in J c and H c2 is still not entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumoto et al reported that enhanced grain connectivity degraded H c2 and flux pinning for nano-SiC doped MgB 2 sintered at high temperature. 16 Moreover, carbon doped MgB 2 has an improved homogeneity at higher processing temperature, as compared to SiC doping. 17 Monofilamentary wires of nominal atomic ratio MgB 2 and MgB 1.9 C 0.1 ͑carbon doped samples͒ were prepared by powder in tube via in situ reaction method, with powders of magnesium ͑99%, −325 mesh͒, amorphous boron ͑99%, 1-2 m͒, and amorphous carbon ͑Ͻ20 nm͒.…”
mentioning
confidence: 99%
“…However, for the undoped and SiC doped MgB 2 , it follows the opposite trend. 16,26 All of this can be understood in terms of carbon substitution being the dominant defect changing the H c2 for nanocarbon doped samples and hence increasing the charge carrier scattering rates. [27][28][29] On the other hand, the drop of H c2 and higher RRR for both undoped and SiC doped MgB 2 sintered at high temperature suggests a reduction of the impurity scattering of charge carriers due to improved crystallnity with high sintering temperature.…”
mentioning
confidence: 99%
“…This is a good indication that CNTs could be aligned along the longitudinal axis of the MgB 2 wires by mechanical drawing in the PIT process. Matsumoto (Matsumoto et al, 2006) reported that J c in SiC-alloyed MgB 2 tapes depends on a complex relation between grain connectivity, H c2 , and flux pinning induced by grain boundaries and precipitates. However, the distinct effect of C incorporation through different routes in J c and H c2 is still not entirely understood.…”
Section: Effect Of Different Kind Of Cnt Addition On the Superconductmentioning
confidence: 99%